THE REPRESENTATION OF GENDER BIAS IN CHILDREN’S LITERATURE KINGDOM TALE COLLECTIONS (Feminist Literary Criticism Review) - Atqi, Atiq Aqiqoqul Hasanah (Universitas Putera Batam, 2022)
The importance of addressing the continuance of gender bias in children's literature cannot be overstated.Considering that children, as the intended audience of children's literature, should be agents of change in society, particularly with relation to gender roles equality.The issue addressed in this study is how women are portrayed in Arleen A. Kingdom Tale Collections, a collection of children's books authored by a woman.The purpose of this paper is to describe and explain the gender bias towards female and male characters in Kingdom Tale Collections.This literary work is created by a woman and will discuss the description of the status and role of women; therefore, feminist literary criticism will be employed as the guiding theory and methodology. This descriptive qualitative research approach obtains its data with a focus on feminism literary critique in the study of literature.The results of this study pertain to the portrayal of gender bias faced by the main female character, including the notion that a woman must be beautiful despite her mental and physical weakness, whereas a guy with a strong body is autonomous and intellectual.Second, the woman must be able to cook and sew for her family, but she cannot pursue a job that is substantially distinct from the male characters. Third, a virtuous woman is shown as possessing a weak and timid disposition. This study concludes that there is still a gender bias in the form of women's domestication as a manifestation of traditional gender norms.